The first data on international multicenter clinical study RheoSTAT-CP0691 on the efficacy and safety of Rheosorbilact® infusion in therapy of purulent peritonitis (Perioperaciina Medicina, 2022)
Generalized forms of peritonitis are a major factor leading to non-traumatic mortality in all cases of emergency care and the second leading cause of sepsis in critically ill patients. Objective of this study was to evaluate the efficacy and safety of multicomponent infusion solution Reosorbilact in the treatment of patients diagnosed with purulent peritonitis. An international multicenter randomized study included 181 patients aged from 18 to 60 years with a diagnosis of purulent peritonitis. Patients received therapy with Reosorbilact according to the prescribing information for use. The primary endpoint of the effectiveness was change in SOFA scale on day 3 of therapy. Changes in APACHE II, SAPS II, MODS, and MPI scores as well as changes in endogenous intoxication markers on day 3 of therapy were considered as secondary endpoints. Safety was assessed by analysis of adverse events (AE) and vital signs after 3 days of therapy. On day 3 of treatment with Reosorbilact statistically significant changes were observed in SOFA (1.80 ± 0.91 points), MODS (1.45 ± 0.76 points) and MPI (1.84 ± 5.03 points) scales. There was a statistically significant improvement in markers of endogenous intoxication (creatinine, bilirubin, white blood cell count, C-reactive protein, neutrophil to lymphocyte ratio) on day 3 of treatment. The majority of AE (98.99 %) were mild. No AE were associated with the study preparation and did not result in the patient’s withdrawal from the study. According to the results of RheoSTAT-CP0691, Rheosorbilact is an effective and safe drug for the treatment of patients with purulent peritonitis. It is advisable to include Rheosorbilact in routine treatment algorithms for patients with purulent peritonitis.
Keywords: abdominal sepsis; septic shock; peritonitis; detoxification therapy; infusion therapy; efficacy; safety; Reosorbilact